An Approach to Adapting a Community-Based Cancer Control Intervention to Organizational Context. Issue 2 (March 2020) - Knott, Cheryl L.; Bowie, Janice; Mullins, C. Daniel; Santos, Sherie Lou Zara; Slade, Jimmie; Rosenberg, Elizabeth; Woodard, Nathaniel; Williams, Ralph; Williams, Randi M.
There has been increasing attention in implementation science to optimizing the fit of evidence-based interventions to the organizational settings where they are delivered. However, less is known about how to maximize intervention–context fit, particularly in community-based settings. We describe a new strategy to customize evidence-based health promotion interventions to community sites. Specifically, leaders in African American churches completed a memorandum of understanding where they were asked to identify two or more health promotion implementation strategies from a menu of 20 and select a planned implementation time frame for each. In a pilot phase with three churches, the menu-based strategy and protocols were successfully implemented and finalized in preparation for a subsequent randomized trial. The three pilot churches identified between two and nine strategies (e.g., form a health ministry, allocate space or budget for health activities, include health in church communications/sermons). The selected strategies varied widely, reinforcing the need for interventions that can be customized to fit the organizational context. Despite the challenges of integrating health promotion activities into non–health focused organizations, this approach has promise for fostering sustainable health activities in community settings.